(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper analyzes the Field Day Theatre Company’s performances wondering whether we are confronted with an experience in a genuinely innovative way of looking at national identity or, rather, this is yet another way to state a different, but little hybrid, representation of Irishness.